An Analysis of Cardiac Disorders Associated With Chimeric Antigen Receptor T Cell Therapy in 126 Patients: A Single-Centre Retrospective Study - Qi, Kunming; Yan, Zhiling; Cheng, Hai; Chen, Wei; Wang, Ying; Wang, Xue; Cao, Jiang; Zhang, Huanxin; Sang, Wei; Zhu, Feng; Sun, Haiying; Li, Depeng; et al. (Frontiers in Oncology, 2021)
Introduction: Chimeric antigen receptor T (CAR-T) cells are effective in treating hematological malignancies. However, in patients receiving CAR-T therapy, data characterizing cardiac disorders are limited. Methods: 126 patients with hematologic malignancies receiving CAR-T cell therapy were analyzed to determine the impact of CAR-T therapy on occurrence of cardiac disorders, including heart failure, arrhythmias, myocardial infarction, which were defined by the Common Terminology Criteria for Adverse Events (CTCAE). Parameters related to cardiac disorders were detected including myocardial enzyme, NT-proBNP and ejection fraction (EF). Cardiovascular (CV) events included decompensated heart failure (HF), clinically significant arrhythmias and CV death. Results: The median age of patients was 56 years (6 to 72 years). 58% patients were male, 62% had multiple myeloma, 20% had lymphoma and 18% had ALL. 33 (26%) patients had cardiac disorders, most of which were grade 1-2. 13 patients (10%) were observed with cardiac disorders grade 3-5, which comprised 5(4%) patients with new-onset HF, 2 (2%) patients with new-onset arrhythmias, 4 (3%) patients with the acute coronary syndrome, 1(1%) patient with myocardial infarction and 1(1%) patient with left ventricular systolic dysfunction. There were 9 CV events (7%) including 6 decompensated heart failure, 1 clinically significant arrhythmias and 2 CV deaths. Among the 33 patients with cardiac disorders, the patients with cardiac disorders CTCAE grade 3-5 had higher grade CRS (grade ≥ 3) than those with cardiac disorders CTCAE grade ≤ 2 (P <0.001). More patients with cardiac disorders CTCAE grade 3-5 were observed in the cohort who did not receive corticosteroids and/or tocilizumab therapy timely comparing with those who received corticosteroids and/or tocilizumab therapy timely (P =0.0004). Conclusions: Cardiac disorders CAR-T cell therapy were common and associated with occurrence of CRS. However, most cases were mild. For patients with CRS grade 3-5, timely administration of corticosteroids and/or tocilizumab can effectively prevent the occurrence and progression of cardiac disorders.